Evaluación del estado ambiental del distrito de Trujillo y su influencia en la construcción de ciudad sostenible - López García, Mercedes (2015)
The purpose of this paper is to compare the environmental status of the district of Trujillo-Peru in 2009 and 2012 and analyze these results using The Model Sustainability developed by Gilberto Gallopín, to determine, whether it contributed to build a Sustainable City. Four aspects were evaluated: Municipal solid waste, water resource, green areas and air quality. For these aspects, 27 variables were identified and data was collected through documentary analysis of public institutions reports, interview with Ing.. Germán Huerta Chombo, advisor to the General Office of SEGAT and perception survey of 450 residents of the district of Trujillo. The results show that 64% (18) of the evaluated variables contributed to the environmental sustainability and 36% (9) of the variables were not useful for that purpose. Furthermore the 60.4% of the pollution believes that environmental status of Trujillo has improved, while 39.6% perceives that nothing or very few actions are done to improve the quality of environment